The Immunogenicity and Safety of Influenza Vaccines among Indonesian Older adult - Dwipa, Lazuardhi; Usman, Stefanie Yuliana; Rakhimullah, Alif Bagus; Mutyara, Kuswandewi; Indrati, Agnes Rengga; Atik, Nur; Muliasari, Rini; Kartasasmita, Cissy (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Immunosenescence, frailty, sarcopenia, and Vitamin D deficiency were thought of having a negative influence on adequate immune response following vaccination. Epidemiological data related to influenza vaccination and its immunogenicity and safety in Indonesia are still scarce. AIM: This study aimed to assess the immunogenicity and safety of the influenza vaccine in older adults in Indonesia and common related conditions. METHODS: This study was a one-group, pre-test, post-test, quasi-experimental study. The vaccine used was a trivalent type. Immunogenicity was assessed according to rate of seropositivity and seroconversion based on hemagglutination inhibition antibody titer. Immunization safety was assessed according to adverse events following immunization (AEFI). RESULTS: A total of 227 subjects were involved in this study. Antibody titers were significantly increased after 28-day influenza vaccination for all strains (p < 0.001). Seropositive rate in 28-day post-vaccination for A/H1N1, A/H3N2, and influenza B was 98.7%, 99.1%, and 97.4%, respectively. Meanwhile, the seroconversion rate for A/H1N1, A/H3N2, and influenza B strains was 54.2%, 66.1%, and 60.4%, respectively. The conditions of the frailty status, sarcopenia, and Vitamin D level were not associated with either seroconversion or seropositive status, both at baseline and endpoint. AEFI was occurred on seven subjects (3.08%) with pain at the injection site and one subject (0.44%) with arm tenderness. CONCLUSION: Influenza vaccination showed adequate immune response and safety regardless of the frailty status, sarcopenia, or Vitamin D level. This result strengthened the importance of influenza vaccine administration in Indonesia older adults.